Body composition assessment using bioelectrical impedance analysis (BIA) in a wide cohort of patients affected with mild to severe obesity. Issue 6 (June 2021) - Brunani, Amelia; Perna, Simone; Soranna, Davide; Rondanelli, Mariangela; Zambon, Antonella; Bertoli, Simona; Vinci, Calogero; Capodaglio, Paolo; Lukaski, Henry; Cancello, Raffaella
Summary: Background & aims: Obesity is characterized by fat mass excess (FM), extra cellular water increase (ECW) and, with ageing, decrease in fat free mass (FFM). The validity of body impedance analysis (BIA) in patients with mild to severe obesity is still debated. The purpose of this study is to describe the Resistance (Rz) and Reactance (Xc) values obtained by Body Impedance Analysis (BIA) in a wide cohort of Italian patients with mild to severe obesity. The secondary endpoint is to describe the resulting body composition values (as percentage and indexes) in this population. Methods: The study enrolled adult in-patients with mild to severe obesity (classified with class I, II and III obesity) undergoing clinical care rehabilitation program for obesity complications and weight loss. BIA values were grouped by sex, BMI and age classes. Results: A total of 8303 patients with obesity, aged 18 to 90 y, were studied. The Resistance (Rz) and Reactance (Xc) were reported by sex, age and BMI classes. In women and men both, the phase angle (PhA) decreases with increasing BMI (kg/m 2 ) and the resulting BIA vector was significantly shifted. The FM index (FMI) was higher (p < 0.0001) in women while FFM index (FFMI) was higher in men (p < 0.0001) and significantly associated with BMI. FFMI decreased with age in both sex (p < 0.0001). Skeletal mass (SM) presents a progressive reduction in relation to age and gender both. Conclusions: The present BIA-based body composition analysis in a wide cohort of mild to severe obese patients revealed a significantly decreased Rz and Xc values with a consequent significant decrease of PhA in a BMI-dependent manner. The body compartments estimation with available equations was BMI, sex and age dependent. These observational results could be the basis for the development of new equations adapted for patients suffering from obesity. Graphical abstract: Image 1 Highlights: BIA in patients with severe obesity is debated. PhA decreases with increasing BMI. BIA ranges in severe obesity were shown.